2023
DOI: 10.1186/s12889-023-15398-0
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of public knowledge of the monkeypox disease in Nigeria

Abstract: The Monkeypox Disease (MPXD) gained attention due to its widened geographical distribution outside of Africa, Hence, a it was declared a global health emergency. The index case in Europe was from a Nigerian traveller. This study assessed public awareness and knowledge of the MPXD by conducting an online, cross-sectional survey of educated Nigerians. A total of 822 respondents were recruited using the snowball sampling method between the 16th to 29th of August 2022. More responses were retrieved from the Northe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…This poor knowledge may be due to the fact that until the recent monkeypox outbreak of 2022, the last time cases of monkeypox were reported in Nigeria was in the 1970s resulting in low level of awareness (10). This finding is similar to that of a study in Nigeria in the general population with only 58.7% having good knowledge of Monkeypox infection (11). In addition, a study Saudi Arabia among the general population reported only 48% of the respondents with high knowledge of monkeypox (9).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This poor knowledge may be due to the fact that until the recent monkeypox outbreak of 2022, the last time cases of monkeypox were reported in Nigeria was in the 1970s resulting in low level of awareness (10). This finding is similar to that of a study in Nigeria in the general population with only 58.7% having good knowledge of Monkeypox infection (11). In addition, a study Saudi Arabia among the general population reported only 48% of the respondents with high knowledge of monkeypox (9).…”
Section: Discussionsupporting
confidence: 87%
“…The range of scores for Attitude was 5-40 using 5point Likert Scale questions while the range of score for Practice was 0-6 using yes or No questions. Knowledge was classified into low (0-7) and high (8)(9)(10)(11)(12)(13)(14), Attitude was classified into low (8-25) and high (25-40) while practice was classified into low (0-3) and high [4][5][6] Content validity of research instrument was determined through expert in the field of p u b l i c h e a l t h a s s e s s i n g t h e r e s e a r c h questionnaire. Observations, corrections and suggestions made were used to revise the instrument before the final draft.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this finding was in contrast with the general population results in Nepal where 53.8% of the study participants had good knowledge; 70 in Saudi Arabia, 48% of the total participants had high knowledge; 71 in Nigeria, 58.7% had good knowledge; 72 in China, 56.5% had a high level of knowledge; 73 in Malaysia, 49.3% of medical students had good mpox knowledge; 74 in Bangladesh, 30.59% medical doctors had good knowledge; 35 55.3% of medical students from 27 low and high-income countries 75 and 26% global healthcare workers had good mpox knowledge. 44 Differences in the study setting, study period, perceptions about mpox infection, source of information, and taking of training could all be contributing factors to this discrepancy.…”
Section: Discussioncontrasting
confidence: 82%
“…The combined prevalence of information sources about the Mpox virus on social networks reached 59% (95% CI 50–68%; 29,146 participants; 22 studies; I 2 = 100%; p < 0.01) (Figure S2 ) [ 22 29 , 31 33 , 35 – 45 ]. On the other hand, access via the internet accounted for 61% (95% CI: 44–77%; 14,002 participants; 5 studies; I 2 = 100%; p < 0.01) (Figure S3 ) [ 30 , 32 , 34 , 35 , 37 ]. As for radio, a level of 10% (95% CI: 07–13%; 8917 participants; 4 studies; I 2 = 93%; p < 0.01) was observed (Figure S4 ) [ 24 , 30 32 ], while television accounted for 24% (95% CI: 09–43%; 14,896 participants; 8 studies; I 2 = 100%; p < 0.01) (Figure S5 ) [ 30 32 , 35 , 37 , 42 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%